Personal finances and their relation with work stress - Kwan Chung, Chap Kau (2023)
The aim of the study was to analyze the relationship between personal finances and work stress, as well as to determine the factors that influence this relationship. As a method, a qualitative approach was used and documentary analyses of thirty articles, theses and reports on personal finance and work stress from the period 2018-2022 were conducted. The results of the studies analyzed suggest that there is an important connection between personal finances and work stress, which would be influenced by factors such as financial education, financial planning, work overload, lack of autonomy and labor conflict. For this reason, it is recommended that companies implement financial education programs and promote a healthy work environment to reduce economic stress and improve the ability to manage economic resources.